Multilevel Analysis of Prognostic Factors for Cognitive Function in Post-Stroke Patients - Utami, Sukandriani; Rahardjo, Setyo Sri; Murti, Bhisma; Novika, Revi Gama Hatta; Tamtomo, Didik Gunawan (Indonesian Journal of Medicine, 2024)
Background: Stroke is the leading cause of disability and the second leading cause of death worldwide. Post-stroke disability can be in the form of motor, sensory, autonomic, or cognitive impairments. Impaired cognitive function is the leading cause of death and pain in post-stroke patients in the world. Decreased cognitive function is present in more than 70% of post-stroke patients and is associated with disability, independence, and pain. This study aims to analyze the prognosis factors of cognitive function in post-stroke patients.Subjects and Method: This study used a cross-sectional design conducted in 7 hospitals on the island of Lombok from July to August 2024. A total of 200 post-stroke patients were selected using stratified random sampling. The dependent variable in this study was cognitive function examined using the Mini Mental State Examinatio (MMSE) questionnaire. Other independent variables such as age, gender, marital status, pension fund, complications, comorbidities and stroke type were collected using a questionnaire. The data were analyzed using a multilevel double-linear regression model.Results: The prognosis factor of cognitive function in post-stroke patients was age (b=-0.19; CI 95%=-0.29 to -0.10; p=<0.001), marital status (b=-3.80; CI 95%=-6.72 to -0.88; p=0.011), pension fund (b=-5.88; CI 95%= -8.35 to -3.42; p=<0.001), complications (b=-5.37; CI 95%= -7.34 to -3.39; p=<0.001). While sex, comorbidities, and stroke type did not show a significant relationship with the cognitive function of post-stroke patients. Conversely, there was an influence of doctors treating post-stroke patients on cognitive function (ICC=8.76%).Conclusion: Age, marital status, pension funds, and complications are prognostic factors in cognitive function of post-stroke patients. Conversely, there is an influence of doctors who treat post-stroke patients on cognitive function.